A review of published anticholinergic scales and measures and their applicability in database analyses. (March 2020) - Lozano-Ortega, Greta; Johnston, Karissa M.; Cheung, Antoinette; Wagg, Adrian; Campbell, Noll L.; Dmochowski, Roger R.; Ng, Daniel B.
Highlights: The properties of available anticholinergic scales and measures vary widely. Two scales and two measures were found to be well suited for administrative data. Methods to characterize anticholinergic burden accounting for dose and potency are lacking. Abstract: Background/objectives: Available metrics for characterizing cumulative anticholinergic exposure over time may not be well suited for use across all US data sources. In this review, the properties of existing anticholinergic scales and measures were evaluated to determine their suitability for implementation in observational studies relying on administrative data. Methods: A targeted literature review was conducted to identify available anticholinergic scales and measures. Suitability of the identified scales and measures for quantification of anticholinergic exposure was evaluated based on pre-defined criteria. Agreement between selected scales was characterized by the percentage overlap of included drugs and inter-scale Spearman's correlation of scores. Results: Sixteen scales were identified; six were relevant and suitable for the quantification of anticholinergic exposure. When implemented on administrative data the Anticholinergic Drug Scale and Anticholinergic Cognitive Burden scale demonstrated the most agreement, with an inter-scale correlation coefficient of 0.82. Scale performance varied by outcome of interest, and underlying disease profile of the population of interest. Variability across the two measures ("average daily dose" and "cumulative dose") was observed, with neither considering both dose and anticholinergic potency in score calculations. Conclusions: Accurate quantification of anticholinergic burden is important in assessing relative risks versus benefits of prescribing anticholinergic medications. In this review, the Anticholinergic Drug Scale and the Anticholinergic Cognitive Burden scale and the average daily dose and cumulative dose measures, were determined to be well suited for the quantification of anticholinergic exposure, particularly in the context of administrative data analyses; however, methods to characterize anticholinergic burden through consideration of both anticholinergic dose and potency are needed.